Teodicea y destinación humana en el joven Kant - Genazzano, Pablo (Con-Textos Kantianos. International Journal of Philosophy, 2019)
The present article aims to inquire the negativity implied in the relation between man and nature in Kant’s early philosophy. This negativity will be treated from the realm of the theodicy as the dimension from where human fate can be posed. The characterization of this fate will be possible via ethical and aesthetic dimensions set out by Kant in his works dedicated to the subject of theodicy and philosophy of nature; i.e. Über Optimismus (in the Lose Bläter), which dates back to the 1750´s. Followingly, we will discuss certain aspects of the author´s Universal History of Nature and Theory of Heaven (1755), and thereafter we will refer ourselves to three minor works concerning earthquakes (1756). In the last chapter we will point out how the comprehension of the aforementioned works are essential in order to define the sentiment of the sublime. In conclusion we will define the sublime as incompatible with optimism.